Immediate implant positioning using tooth‐derived bone substitute material for alveolar ridge preservation: Preliminary results at 6 months. Issue 1 (10th November 2022) - Taschieri, Silvio; Morandi, Benedetta; Alberti, Alice; Tarasenko, Svetlana; Diachkova, Ekaterina; Francetti, Luca; Corbella, Stefano
Abstract: Objectives: In the present study we evaluated the effectiveness of the use of a novel autologous bone substitute derived directly from processing the extracted tooth in the upper premolar area to preserve a suitable esthetic score and functionality. Material and Methods: Fourteen bone‐level implants with platform switching were inserted in 12 patients immediately after atraumatic extraction of premolars for restorative or endodontic reasons. The implant buccal bone gap was filled using autologous tooth extracted‐derived material. Clinical and radiographic parameters, including Pink Esthetic Score (PES) were evaluated at 6 months. Results: A total of 10 patients accounting for 11 implants were included. PES showed a suitable esthetic result, and all the implant‐prosthetic rehabilitation reported full satisfaction for masticatory function, phonetics, and aesthetics. Bone levels were stable and not affected by implant location, lesion type, or bone quality. Conclusion: Radiographically the autologous bone substitute used appears stable in the surgical site and there is good continuity between the autologous bone and the graft. No adverse effects such as periodontal inflammation, infection, or graft rejection was reported.